Radiographic analysis of the sacral-2-alar screw trajectory - Yulin Zhao; Baisheng Yuan; Yijun Han; Binglei Zhang (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Purpose To explore the feasibility of sacral-2-alar (S2-alar) screw placement by measuring the length, diameter, and angle of the screw trajectory on computed tomography (CT). Methods This study selected 100 Han-nationality adults in northern China with a normal spine and pelvis. CT data were imported into PHILIPS software for reconstructing the 3D digital images. The optimal S2-alar screw trajectory was imitated on CT. Parameters including the length of the screw trajectory, sagittal angle, coronal angle, distance between the entry point and the spinous process, and minimum diameter of the screw trajectory were measured to evaluate the application of S2-alar screws. Results In total, 48 males and 52 females were included. The average length of the left screw trajectory was 47.18 ± 3.91 mm. The sagittal angle was 29.06 ± 4.00°. The coronal angle was 13.31 ± 6.95°. The distance between the entry point and the spinous process was 21.0 (3.7) mm. The minimum diameter of the screw trajectory was 17.1 (2.3) mm. The average length of the right screw trajectory was 45.46 ± 4.37 mm. The sagittal angle was 23.33 ± 4.26°. The coronal angle was 14.88 ± 6.84°. The distance between the entry point and the spinous process was 22.8 (2.9) mm. The minimum diameter of the screw trajectory was 16.9 (3.1) mm. In women, the average length of the left screw trajectory was 44.80 ± 3.66 mm. The sagittal angle was 32.14 ± 5.48°. The coronal angle was 16.04 ± 7.74°. The distance between the entry point and the spinous process was 21.8 (2.8) mm. The minimum diameter of the screw trajectory was 17.1 (5) mm. The average length of the right screw trajectory was 44.01 ± 3.72 mm. The sagittal angle was 25.12 ± 5.19. The coronal angle was 16.67 ± 8.34°. The distance between the entry point and the spinous process was 21.6 (2.7) mm. The minimum diameter of the screw trajectory was 17 (4.5) mm. As seen from the data, there were significant differences in the minimum diameter of the screw trajectory in both males and females. In females, there were also significant differences between the left and right sides in the coronal angle. Between males and females, there were statistically significant differences in the length of the screw trajectory. There were no statistically significant differences in the other parameters between males and females. Conclusion The optimal screw trajectory of the S2-alar screw can be found on CT. The length and deflection angle of the screw meet the clinical requirements. This method is easy to perform and feasible for clinical application.